Community Satisfaction Index In Seluma Selatan Village Office Services, Seluma Selatan District, Seluma Regency - Rama Triansyah Putra; Suswati Nasution; Iswidana Utama Putra (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The purpose of this study was to determine the Community Satisfaction Index in the Services of the Sengkuang Village Office, Seluma Selatan District, Seluma Regency with Permenpan No. 14 of 2017 on 9 elements. This research method is descriptive quantitative with accidental sampling technique. The sample of this study was 110 respondents in the form of the IKM value calculated using the weighted average value of each service element. The results of this study indicate that the service at the Sengkuang Village Office, Seluma Selatan District, Seluma Regency on the requirements shows an IKM conversion value element of 93.75, with a very good category, systems, mechanisms and service procedures with an IKM conversion value element of 76.00, with a Poor category, Time completion with an IKM conversion value element of 76.25, in the Poor category, Costs/tariffs with an IKM conversion value element of 96.00, in the Very Good category, Product specifications for the type of service on an IKM conversion value element of 93.75, with a Very Good category, Implementing competence with the element of the IKM conversion value is 94.00, with the Very Good category, the behavior of the implementer with the result of the IKM conversion value of 88.00 in the Good category, Handling of suggestions and input complaints shows the IKM conversion value of 94.00 in the Very Good category, and Means shows the IKM conversion value of 93.25 with very category Well. So, the IKM at the Sengkuang Village Office, Seluma Selatan District, Seluma Regency is 80.50 with a service quality B and the service rating is good, because it is in the interval value of 76.61 - 88.30.